Biolinguistic Foundations of Early Childhood Education: Exploring the Interplay Between Biological Predispositions and Pedagogical Practices in Language Development (Global Journal of Human-Social Science, 2025)
This paper examines the intersection of biolinguistic theories and early childhood education emphasising how biological predispositions and environmental factors influence language acquisition Biolinguistic theories posit that humans are biologically equipped to learn language but the environment plays a role in shaping language skills The review examines current research on the biological foundations of language development including the role of Universal Grammar critical periods and brain plasticity Additionally it discusses how pedagogical practices such as interactive reading social interaction and bilingual education enhance language learning By integrating these biological and pedagogical perspectives this paper aims to inform strategies in early childhood education that foster language acquisition and literacy The findings suggest that early rich linguistic environments are vital for maximising language development particularly for children from disadvantaged backgrounds Further research is needed to refine pedagogical practices in diverse cultural and educational contexts
Keywords: biolinguistics; language development; early childhood education; bilingualism; pedagogical practices